2022
DOI: 10.1680/jensu.21.00033
|View full text |Cite
|
Sign up to set email alerts
|

Engineering nature-based solutions: examining the barriers to effective intervention

Abstract: A growing body of research is examining how Nature-Based Solutions (NBS) are offering planners, politicians and engineers options to promote respond to a wide range of biophysical and socio-economic problems. However, despite the increasing popularity of NBS, there is limited analysis available on how these ‘solutions’ align with urban problems, at what scale they are most effective, and what costs are associated with investment in urban nature. This paper analyses current approaches to urban sustainability vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…A further commonality across these debates is the framing of NBS as a facilitator of more effective human/environmental discussions-one where nature offers direct solutions to human (and ecological) problems [19,34,38]. Within the URBAN GreenUP project, links between the ecological benefits and the associated socio-economic opportunities afforded by NBS interventions have been central, e.g., enhancing recreation, access to nature, and economic development [39]. Against this backdrop, each of the five-year Horizon 2020 R&I programs tested a range of delivery options to examine how NBS can create more sustainable and functional urban environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further commonality across these debates is the framing of NBS as a facilitator of more effective human/environmental discussions-one where nature offers direct solutions to human (and ecological) problems [19,34,38]. Within the URBAN GreenUP project, links between the ecological benefits and the associated socio-economic opportunities afforded by NBS interventions have been central, e.g., enhancing recreation, access to nature, and economic development [39]. Against this backdrop, each of the five-year Horizon 2020 R&I programs tested a range of delivery options to examine how NBS can create more sustainable and functional urban environments.…”
Section: Discussionmentioning
confidence: 99%
“…All of these are common to each Horizon 2020-funded NBS project and are identified as key factors influencing the framing of NBS in the literature. The evidence discussed above and the wider reporting on the Horizon 2020 NBS projects provide opportunities to reflect on what best practice for NBS looks like, even if the NBS interventions delivered in Liverpool do not fully align with these goals [19,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Mohommad and Pugacheva (2022) revealed that the pandemic made people realize the significance of a healthy nature and the need for green recovery since a study by Castellar et al (2021) uncovered that nature is interpreted by people as a green factor and defined with the presence of vegetation. Lately, the approach to restoring and increase the quality and the number of green spaces and the classical perception of the water-urban ecosystem interaction in urban areas changed to Naturebased Solutions (NbS), which was first used by the International Union for Conservation of Nature (IUCN) in the early 2000s (Mell et al, 2022;OECD, 2020;Krauze & Wagner, 2019). NbS have different definitions in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…NbS have different definitions in the literature. Mell et al (2022) defined NbS as a set of aid tools to cities in terms of preventing and reducing the biophysical environment problems including climate change effects, ecological losses, risk of flooding and air quality. Frantzeskaki et al (2017) defined NbS as transition initiatives with solutions to restore nature, imitate nature and build upon nature to address place-specific environmental problems.…”
Section: Introductionmentioning
confidence: 99%